Klasyfikacja metod zbierania danych o rynkach zagranicznych ze źródeł pierwotnych - Kaczmarczyk, Stanisław (Classification of Methods of Gathering Data about Foreign Markets from Primary Sources, 2006)
Polish enterprises mostly explore the secondary data sources in their research of foreign markets. Primary sources are still rarely used. Methods of data gathering (data about foreign markets from primary sources) do not have to be very expensive. Most of these methods are very well known. They belong both to direct and indirect survey methods. The first ones are more cheaper in foreign markets research. Within the last 10 years survey methods have been applied through the Internet. This was resulted in further reduction of the foreign markets research costs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 48-58